Determinants of commercial bank profitability in Malaysia / Siti Sharina Saridi - Saridi, Siti Sharina (Faculty of Business and Management, 2015)
The aim of this study is to determine the effect of bank characteristic (internal determinations) on the profitability (return on asset) of commercial bank in Malaysia. Internal determinants are like bank size, capital adequacy, liquidity risk and asset quality. Secondary data was collected from seven commercial bank in Malaysia from 2005 to 2011. The financial ratio technique was applied to calculate on the variable and Ordinary Least Square method was used to run the regression model. The estimation result shows that bank size and capital adequacy are significantly and positively influence the bank profitability while liquidity risk and asset quality are inversely affect the commercial bank profitability.